Strategy of Platform Music Streaming Langit Musik Application to Improve Monthly Active Users Through Customer Acqusition and Customer Retention - Sarah Permana, Nabila; Furinto, Asnan (The Indonesian Journal of Business Administration, 2019)
Abstract. Digital technology is cannot be separated from human life. Nowadays most of the human activities are using a smartphone. Related to hobbies or commonly called digital lifestyles, such as playing games, watching videos, and listening to music can easily be accessed using a smartphone. Based on Annie's app in 2018, Indonesia ranks first as the country that uses the smartphone for the longest time. using a smartphone with an average of 4 hours of smartphone use a day for playing games, watching videos, and listening to music can easily be accessed using a smartphone. This circumstance becomes an opportunity for telecommunication companies to support Indonesia's digital lifestyle improvement by providing services and product related. Listening songs with music streaming on smartphones are the largest mobile activity in Indonesia. However Telkomsel have music streaming product, Langit Musik as a Indonesia music streaming application, is still facing a difficulty on acquiring and maintain their users where monthly active user for Langit Musik from App Annie in 2018 shows that the monthly number of active users of Langit Musik for 6 months dropped from 400,000 users to 155,000 users and the position of Langit Musik application among the competitors is the lowest. To analyze this problem, there are several analysis that has been done to analyze the current condition of Langit Musik. The first step is to analyze the internal condition of Langit Musik, second is to analyze the external force of the company. Next, is to analyze the Langit Musik problem using thematic frames work; Customer Journey to analyze for the Customer of Langit Musik and The Five's Analysis for those who have not used the Langit Musik Application. This analyze is done by conducting a questionnaire and observation during the internship period and discuss with the product development manager.KEYWORDS: Langit Musik, Customer Acquisition, Customer Retention, Customer Journey, Marketing Strategy, Music Streaming, Telkomsel,